1. The problem statement, all variables and given/known data Solve: y'' + y' - 2y = 0 y(0) = 1 y'(0) = -2 2. Relevant equations 3. The attempt at a solution I found: http://image.cramster.com/answer-board/image/cramster-equation-200942414569633761817696516250247.gif So the recurrence relation is: http://image.cramster.com/answer-board/image/cramster-equation-20094241457286337618184812037502167.gif for n = 0: http://image.cramster.com/answer-board/image/cramster-equation-20094241458446337618192469850005024.gif Now here's my question. Can I assume at this point that: c0 = y(0) = 1 and c1 = y ' (0) = -2 ? This would allow me to have a numerical value for each cn. Thanks!